A Child Infected with COVID-19 in China—A Case Report. (18th August 2021) - Lin, Chunxia; Zhong, Beilong; Zheng, Fangfang; Guo, Xinming; Guo, Yi; Deng, Zhizhong; Zhou, Chuanxin; Guo, Yangbin
Abstract: A 16-month-old boy was admitted with cough for 2 days and fever for 1 day. Chest computed tomography (CT) scan of the child revealed large areas of ground-glass opacities in both lungs. Nucleic acid amplification tests (NAATs) were performed repeatedly to detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), but the results were all negative. On day 13 of hospitalization, no clinical symptoms except diarrhea were present in the patient, and re-examination by chest CT revealed lesion shrinkage, but the NAAT on throat swabs was positive. On day 22 of hospitalization, the NAAT on throat swabs was negative and the fecal samples were positive. Positive fecal samples nucleic acid lasted for 62 days. Suggesting that pediatric patients may be important sources of infection during the recovery phase of clinical symptoms and whether SARS-CoV-2 has fecal–oral transmission needs further study.